2017
DOI: 10.1063/1.5018528
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of emission characteristics and noise test of an I.C. engine using different biodiesel blends

Abstract: Flat plate solar collector for water pre-heating using concentrated solar power (CSP) AIP Conference Proceedings 1919, 020021 (2017) Abstract. Biodiesel is a captivating renewable resource providing the potential to reduce particulate emissions in compressionignition engines. A comparative study is conducted to evaluate the effects of using biodiesel on exhaust emissions. Exhaust smokiness, noise and exhaust regulated gas emissions such as carbon di oxides, carbon monoxide and oxygen are measured. It is observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Therefore, in both the driver and bystander's positions, the B 25 E 4 D 71 fuel was identified as the blend with producing the least noise pollution. By increasing the percentage of biodiesel in the fuel blend, the noise pollution is reduced that concurs with the results of other studies [24,[27][28][29]33] whereas not agreeing with the results obtained by Li et al [31].…”
Section: The Stationary Modesupporting
confidence: 65%
See 2 more Smart Citations
“…Therefore, in both the driver and bystander's positions, the B 25 E 4 D 71 fuel was identified as the blend with producing the least noise pollution. By increasing the percentage of biodiesel in the fuel blend, the noise pollution is reduced that concurs with the results of other studies [24,[27][28][29]33] whereas not agreeing with the results obtained by Li et al [31].…”
Section: The Stationary Modesupporting
confidence: 65%
“…The effect of applying fuel blends on the performance of a four-cylinder engine and noise and air pollution was investigated. The results of this study revealed that although biodiesel fuel blend provided a slight change in engine performance compared to pure diesel, noise pollution decreased with increasing biodiesel percentage [27][28][29].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…MgO, SrO, and ZnO are other nanocatalysts utilized in the transesterification procedure. Again, Fe 3 O 4 , CuFe 2 O 4 , activated carbon, and other materials can be used to enhance these catalysts' characteristics [24][25][26][27][28][29][30][31].…”
Section: Role Of Nanomaterials In Biodiesel Productionmentioning
confidence: 99%
“…The ideal biodiesel production feedstock includes edible oil sources such as palm, sunflower, soybean, olive, maize, rapeseed, safflower, peanut, and coconut oil [26]. Table 1 provides an overview of the use of nanocatalysts for manufacturing biodiesel from vegetable oil, waste cooking oil (WCO) extracted from animal fat, and algal oil for different operation conditions.…”
Section: Role Of Nanomaterials In Biodiesel Productionmentioning
confidence: 99%